ANALISA AKAR MASALAH PENYEBAB LAYANAN POLI GERIATRI YANG BELUM BERJALAN OPTIMAL DI RUMAH SAKIT “X” - Arisetiawan, Muhammad Taufiq (Jurnal Administrasi Publik, 2024)
Root Cause Analysis of The Unoptimal Geriatric Polyclinic in The “X” Hospital. The elderly population in Malang is expected to reach 2 million by 2050, with 80,430 people in the outpatient unit. The geriatric polyclinic at Panti Waluya Sawahan Malang Hospital targets patients aged 65 and older with multiple physical illnesses. However, the hospital's readiness to organize geriatric services has not met the required standards. A study using semi-structural interviews and discussions with related units revealed several influencing factors, including lack of training, absence of specialized officers, and limited human resources. Patients have their own choice of polyclinic, and there is a lack of informative information about geriatric services. The hospital's official website and guidelines have not been reviewed since 2018, and media and communication about geriatric services are lacking. Facilities standards are not met, and some patients are unaware of the services.